2017
DOI: 10.1536/ihj.16-226
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Congestive Heart Failure Due to Severe Aortic Valve Stenosis With Low Dose Tolvaptan in Elderly Patients

Abstract: SummaryMedical therapy for severe aortic valve stenosis (AS) is necessary for inoperable patients due to comorbid conditions. Tolvaptan (TLV), unlike other diuretics, resulted in modest changes in filling pressures associated with an increase in urine output, suggesting that TLV improves congestive heart failure (CHF) due to severe AS without hemodynamic instability.We retrospectively investigated 14 consecutive patients ≥ 80 years of age admitted due to decompensated CHF with severe AS at Juntendo University … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Takasu et al reported that low-dose TLV therapy for elderly AHF patients with severe aortic stenosis resulted in decongestion without causing hemodynamic instability. 28 Their patients were given a lower dose of TLV (4.8 + 1.8 mg daily) than in the present study (7.2 + 1.8 mg daily).…”
Section: Administration Of Low-dose Tlvmentioning
confidence: 50%
“…Takasu et al reported that low-dose TLV therapy for elderly AHF patients with severe aortic stenosis resulted in decongestion without causing hemodynamic instability. 28 Their patients were given a lower dose of TLV (4.8 + 1.8 mg daily) than in the present study (7.2 + 1.8 mg daily).…”
Section: Administration Of Low-dose Tlvmentioning
confidence: 50%
“…26) In terms of increasing serum sodium levels, the vasopressin V2 receptor antagonist tolvaptan is the reasonable option since it acts directly against ADHF-associated enhanced AVP secretion. [27][28][29] Indeed, in the Efficacy of Vasopressin Antagonism in Heart Failure Outcome Study With Tolvaptan (EVEREST), tolvaptan significantly increased the serum sodium concentration in hyponatremic patients hospitalized with ADHF. 30) In a post hoc analysis of the Acute and Chronic Therapeutic Impact of a Vasopressin Antagonist in Chronic Heart Failure trial in which patients hospitalized for ADHF were randomized to placebo or one of 3 tolvaptan doses to investigate its effects on 60-day mortality, hyponatremic patients with a serum sodium improvement (!2 mmol/L increased from admission to discharge) had better 60-day mortality rates compared to those showing no improvement, 31) suggesting the therapeutic potential of tolvaptan on admission hyponatremia in patients hospitalized with ADHF.…”
Section: Discussionmentioning
confidence: 99%
“…Tolvaptan is an oral selective V2 receptor antagonist that increases net volume loss in patients with HF without adversely affecting hemodynamics [9,12,15,16]. Previous pilot studies demonstrated the safety and efficacy of tolvaptan treatment in patients with HF and severe AS [17,18]; however, these studies did not fully clarify its safety and efficacy based on a prospective multicenter design. The present LOHAS registry showed comparative results with these previous reports, demonstrating increased urine output, reduced body weight, and improved symptoms and serum BNP levels without affecting blood pressure, heart rate, and renal function even in elderly patients with severe AS.…”
Section: Discussionmentioning
confidence: 99%